2003
DOI: 10.1148/radiol.2272020293
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Screening with CT Colonography, Colonoscopy, and Double-Contrast Barium Enema Examination: Prospective Assessment of Patient Perceptions and Preferences

Abstract: Patients undergoing colorectal cancer screening prefer CT colonography to both colonoscopy and DCBE. The majority of patients experience discomfort and inconvenience with cathartic bowel preparation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
128
1
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(137 citation statements)
references
References 16 publications
3
128
1
5
Order By: Relevance
“…Data from large studies on screening cohorts have suggested that CTC and conventional colonoscopy have similar sensitivity for polyps ≥6-mm in diameter [8,9]. Moreover, patients generally prefer CTC instead of barium enema examination or colonoscopy [10][11][12][13]. However, concerns were raised about recommending CTC as routine screening tool because of potential harm [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Data from large studies on screening cohorts have suggested that CTC and conventional colonoscopy have similar sensitivity for polyps ≥6-mm in diameter [8,9]. Moreover, patients generally prefer CTC instead of barium enema examination or colonoscopy [10][11][12][13]. However, concerns were raised about recommending CTC as routine screening tool because of potential harm [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…However, it remains to be demonstrated if the advantages conferred by CO2 are sufficiently significant to improve patient acceptance of endoscopic procedures and cost-effectiveness (by reducing loss from normal activities after endoscopy). These two criteria, namely patient acceptance and cost-effectiveness, are of paramount importance for colorectal cancer screening as computed tomography (CT) colonography has been shown to be superior to colonoscopy for both of them [20,21] . Incidentally, one of the three CO2 insufflators that are available for endoscopy was developed initially for gut distension during CT colonography, and radiologists use it increasingly often for reasons of safety and patient comfort (CO2 is used in about half of CT colonographies) [22] .…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of laxative ftCTC cases may provide excellent conditions for the application of automated imageprocessing methods, the requirement of laxative bowel cleansing is also considered to be one of the major barriers for patient adherence to colorectal cancer screening guidelines (Gluecker et al (2003); Beebe et al (2007)). Efforts to minimize this burden are under investigation and include, for example, structured low-fiber diets and complete elimination of the laxative dose (Lefere et al (2002); Zalis et al (2003); Iannaccone et al (2004)).…”
Section: Discussionmentioning
confidence: 99%